Wage Posting or Wage Bargaining? A Test Using Dual Jobholders - Lachowska, Marta; Mas, Alexandre; Saggio, Raffaele; Woodbury, Stephen A. (Journal of Labor Economics, 2022)
We employ a revealed preference test to distinguish between wage posting and wage bargaining. Using a sample of dual jobholders in Washington State, we estimate the sensitivity of wages and separation rates to wage shocks in a secondary job. In lower parts of the wage distribution, improvements in the outside option lead to higher separations rates but not to higher wages, consistent with wage posting. In the highest wage quartile, improved outside options translate to higher wages but not higher separation rates, consistent with bargaining. In the aggregate, bargaining appears to be a limited determinant of wage setting.